Employing Strategic Procurement of Booklets to Enhance Employee Reading Interests - Nabila, Thifal Khansa; Subiyantoro (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This research aims to explore the potential of using booklets to stimulate reading interest among employees at the Education Quality Assurance Center (BPMP) D.I. Yogyakarta, thereby addressing the gap in understanding adult reading interest within professional or workplace environments and specifically in non-formal educational settings like libraries. Design/methods/approach – A qualitative approach was employed in this research, leveraging techniques such as observations, interviews, and documentation analysis—the study methodology involved observing employees' behavior, conducting in-depth interviews, and examining available written data. Findings – The study's findings indicate that providing booklets can effectively enhance employee reading interest. Other methods also emerged from the survey, including enhancing library resources, creating immersive experiences, and promoting reading culture through supportive government initiatives. Research implications/limitations – This study provides a rich understanding of the factors affecting reading interest in a non-formal educational setting. It offers recommendations to improve the state of adult literacy and academic quality. However, the limitations of this study, such as reliance on self-reported data and limited sample size, highlight the need for future research to confirm these findings and explore other potential interventions and contexts. Practical implications – The findings offer valuable insights for educational institutions, specifically non-formal educational settings, to improve employee reading interest, thereby contributing to national literacy rates and overall academic quality. Originality/value – This study adds to the literature by comprehensively examining the factors influencing reading interest in professional and non-formal educational environments. Furthermore, it suggests practical strategies that can be implemented to stimulate reading interest among adults.